Concise Stereoselective Total Synthesis of (−)-Hedycoropyran A - Ahn, Byeongyeon; Lee, Ryangha; Kim, Hyoungsu; Lee, Dongjoo (Journal of Organic Chemistry, 2023)
A concise and stereoselective total synthesis of (−)-hedycoropyran A was accomplished in a substrate-controlled manner from a readily available alkene. Highlights of the synthesis include a highly diastereoselective dehydrogenative cycloetherification to construct the trans-2-aryl-6-alkyl-3,6-dihydro-2H-pyran framework and late-stage substrate-controlled trans-dihydroxylation at C(3,4).
Keywords: Cycloetherification; Diastereoselective; Dihydroxylation; Late stage; Stereo-selective; Total synthesis